Aksesibilitas Pariwisata Bagi Difabel di Kota Surakarta (Studi Evaluasi Peraturan Menteri Pekerjaan Umum Nomor 30 Tahun 2006 Tentang Pedoman Teknis Fasilitas Dan Aksesibilitas Pada Bangunan Gedung Dan Lingkungan) - Rina Herlina Haryanti; Candra Sari (Universitas Sebelas Maret, 2017)
This study aims to look at the complete facilities and their accessibility in existing tourist sites in the city of Surakarta namely Taman Balekambang, Taman Satwa Taru Jurug and Taman Hiburan Rakyat (THR) Sriwedari. Completeness of facilities and existing facilities at tourist sites is assessed based on the Minister of Public Works No. 30 Year 2006 on Technical Guidelines and Accessibility Facility On Building and Environment. This study assessed whether tourism in Surakarta was accessible or not and viewed based principles of accessibility. The method used is descriptive qualitative research with data collection technique using observation, interviews and documents. To obtain valid data, this study using triangulation of data sources. While data analysis techniques using interactive analysis techniques.Facilities were seen and assessed based on the Public Works Ministerial Regulation No. 30 Year 2006 on Technical Guidelines and Accessibility Facility Building and Environment On the basis of the size of the room, pedestrian paths, guide lines, parking areas, ramps, and traffic signs and markings. The results showed that the state of the facilities and existing facilities at tourist sites namely Taman Balekambang, Taman Satwa Taru Jurug and Taman Hiburan Rakyat (THR) Sriwedari yet complete and in accordance with policy. Incompleteness of this facility shows that tourist sites are not accessible for the disabled. It makes the accessibility of tourism in Surakarta not materialized.